Spiritualitas dan Tantangan Modernitas (Studi Terhadap Manifestasi Neo-Sufisme Fazlur Rahman) - Fajri, Afuza; S, Syukri; Siregar, Muhammad Nuh (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Community life continues to develop according to the times, without realizing it directly or not, influencing attitudes and patterns of life in the changes faced by society. These changes will affect civilization both positively and negatively. Fazlur Rahman initiated Neo-Sufism to face the spiritual crisis in modern society. The problem formulation in this research is; What is Fazlur Rahman’s cencept of Neo-Sufism and How is it manifested in overcoming the spiritual crisis in modern society? This research aims to deepen knowledge regarding the manifestation of Fazlur Rahman’s concept of Neo-Sufism in the spirtual crisis and challenges of modern society. This research is a type of Library Study Research using a philosophical approach method with historical theory. So it can be concluded that Fazlur Rahman’s concept of Neo-Sufism is an attempt to reaffirm complete islamic values, a balanced life in all aspects of life and in terms of human expression. And its manifestation is in overcoming the spiritual crisis in modern society, namely by renewing religious understanding with efforts to reconstruct asceticism in overcoming spirituality in modern society. Neo-Sufism aims to restore modern society to balance with this world and the afterlife.